Answer :

Let, f (x) = x3-23x2+142x-120

The factors of the constant term – 120 are


Putting x = 1, we have


f (1) = (1)3 – 23 (1)2 + 142 (1) – 120


= 1 – 23 + 142 – 120


= 0


So, (x – 1) is a factor of f (x)


Let us now divide


f (x) = x3-23x2+142x-120 by (x - 1) to get the other factors of f (x)


Using long division method, we get


x3-23x2+142x-120 = (x – 1) (x2 – 22x + 120)


x2 – 22x + 120 = x2 – 10x – 12x + 120


= x (x – 10) – 12 (x – 10)


Hence, x3-23x2+142x-120 = (x – 1) (x - 10) (x - 12)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the vaRS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

If <span lang="ENNCERT Mathematics Exemplar

Show that p – 1 iNCERT Mathematics Exemplar

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the value ofNCERT Mathematics Exemplar

In each of the foRD Sharma - Mathematics